La relación nacional-departamental en Bolivia: una mirada multinivel al nuevo escenario político del país - Ascarrunz, Julio (2015)
This article focuses on party competition in Bolivia from a multilevel approach with department (intermediate level) as the territorial unit of analysis from 2005 to 2015. The objective is to demonstrate the (in)congruence of an institutional level overlooked by the literature on multilevel studies, for which two indices of measurement are used: Summary Measure of Congruence (Gibson and Suarez-Cao 2010) in a one version and Dissimilarity Index (Johnston 1980) in two versions, nationally aggregated and departmentally disaggregated, with voting data from all competing parties (DISa) and only from those with double competition (DISb). The argument handled is that if an institutional level is important enough to be introduced to the electoral framework of a country, it should also be important enough for academic interest, especially in their relation with the rest of the system. From this, the study concluded that the importance of this institutional level depends on the degree of autonomy it has and the interest of the partisan actors and regional elites.